Impact of Albumin Binding Function on Pharmacokinetics and Pharmacodynamics of Furosemide - Gerd Klinkmann; Sebastian Klammt; Malte Jäschke; Jörg Henschel; Martin Gloger; Daniel A. Reuter; Steffen Mitzner (Medicina, 2022)
Background and Objectives: Albumin binding of the loop diuretic furosemide forms the basis for its transport to the kidney and subsequent tubular secretion, which is a prerequisite for its therapeutic effects. Accordingly, high albumin concentrations should result in higher efficacy of furosemide. However, study results on the combination of furosemide in conjunction with albumin, and on the efficacy of furosemide in hypoalbuminemia, did not confirm this hypothesis. The aim of this study was to determine the efficacy of furosemide not only in relation to albumin concentration, but also taking albumin function into account. Materials and Methods: In a prospective and non-interventional clinical observational trial, blood and urine samples from 50 intensive care patients receiving continuous intravenous furosemide therapy were evaluated. Albumin binding capacity (ABiC) determination allowed conclusions to be drawn about the binding site-specific loading state of albumin, by quantifying the unbound fraction of the fluorescent marker dansylsarcosine. In addition, assessment of the total concentration of furosemide in plasma and urine, as well as the concentration of free furosemide fraction in plasma, was performed by HPLC–MS. The efficacy of furosemide was evaluated by the ratio of urine excretion to fluid intake. Results: In patients with an ABiC ≥ 60% free furosemide fraction was significantly lower compared to patients with a lower ABiC (p < 0.001), urinary furosemide concentration was higher (p = 0.136), and a significantly higher proportion of infused furosemide was excreted renally (p = 0.010). ABiC was positively correlated (r = 0.908, p = 0.017) with increase in the urine excretion to fluid input ratio after initiation of furosemide therapy. Conclusions: ABiC could serve as a marker for individual response to furosemide and could be used to generate patient-specific therapeutic regimens. In view of the relatively low number of patients in this study, the relationship between furosemide efficacy and albumin function should be investigated in larger studies in the future.